Triplet exciton formation ratio in poly(p-phenylene-vinylene) light-emitting diode - Lin, LC; Meng, HF; Shy, JT; Horng, SF; Yu, LS; Chen, CH; Liaw, HH; Huang, CC; Peng, GY; Chen, SA (My University, 2003)
The triplet to singlet exciton formation ratio in a poly(2-methoxy-5(2'-ethyl-hexyloxy)-1,4-phenylene vinylene) (MEH-PPV) light-emitting-diode is measured by comparing the triplet induced-absorptions with optical and electric excitations at same singlet exciton density. The ratio is a strong universal decreasing function of the averaged electric field. Using 4 ns for singlet to triplet intersystem crossing time, the ratio is significantly larger than the spin-statistics value 3 at intermediate field but is reduced to about 1 for higher field.
Keywords: triplet exciton; light-emitting-diode